Sosoalisasi Pemanfaatan Rumput Vetiver (Chrysopogon zizanioides) Dalam Mitigasi Bencana Longsor di Desa Gelangsar, Kabupaten Lombok Barat - Arben Virgota; Baiq Farista; Suripto; H.A. Jupri; Nur Indah Julisaniah; Aida Muspiah (Jurnal Pengabdian Magister Pendidikan IPA, 2022)
Gelangsar Village, West Lombok is one of the villages located in a hilly area which resulted in several points in the village of Gelangsar experiencing landslides. The topography which is hilly and steep, triggers landslides in the village of Gelangsar. In addition, the relatively high rainfall in the last few months has made the soil conditions more flexible. Areas that have the potential to cause landslides can be overcome by planting plants that can bind the soil tightly so that it can overcome the potential for landslides. Therefore, this service aims to socialize the use of vetiver grass as a bioengineering method in managing landslides in Gelangsar Village, Gunungsari, West Lombok. This Community Service activity uses the counseling method and the creation of a pilot project. Counseling was conducted to introduce vetiver grass plants and their cultivation techniques. Making a pilot project (pilot project) have been done in the homes of residents who are partners. The Pilot Project was created as a media for socialization and as a strategy for efficiency and effectiveness for target activities. The community of partners are willing to implement and develop vetiver grass as a biotechnology agent to prevent erosion and also as an economic opportunity. This programme has been able to provide knowledge in mitigation landslide disaster management activities independently. Planting vetiver grass is expected to be able to reduce the risk of erosion at landslide-prone points in the village of Gelangsar, improve the physical condition of the land and increase land productivity.